Analisa Perbandingan Biaya Penggunaan Scaffolding Ringlock dan Scaffolding Frame Proyek Pembangunan MCC Room IPA Bekasi - Ma’arif, Aziz; Kartika, Nia; Tahadjuddin, Tahadjuddin (Jurnal Talenta Sipil, 2025)
Scaffolding is one of the critical supporting elements in construction projects, scaffolding functions to withstand loads and allow the implementation of work at height. The tool is designed to provide temporary support for workers as well as materials, ensuring stability and safety during construction projects. Along with the development and progress in the construction industry, various new innovations of scaffolding types continue to emerge. Given the importance of this supporting element in supporting the running of construction projects, the selection of improper scaffolding can have a significant impact on the construction project that is being carried out. The purpose of this study is to review the efficiency of the use of scaffolding in construction work, by comparing ringlock scaffolding with frame scaffolding reviewed in terms of cost to determine which type is more efficient to use according to the needs of the project. This study uses a descriptive method and a comparative method, the descriptive method aims to describe and calculate the cost of ringlock and scaffolding frame scaffolding costs, while the comparative method is used to make a comparison between the two, so that the comparative cost of each type of scaffolding can be obtained. The results of the analysis obtained the results of the calculation of the cost of scaffolding ringlock and scaffolding frame needs from an area of 821.05 m2, the rental price of ringlock scaffolding is Rp. 109.311.600, while the rental cost of scaffolding frame is Rp. 89.223.600. Meanwhile, the cost of buying a ringlock scaffolding is Rp. 955,342,000, while the cost of buying a scaffolding frame is Rp. 808.229.000. The cost of installing and dismantling ringlock scaffolding is Rp. 4.034.625 and scaffolding frame is Rp. 8.040.125. The end result of the comparison of ringlock scaffolding and scaffolding frame for installation costs is cheaper than ringlock scaffolding but for rental and purchase costs are higher ringlock scaffolding compared to frame scaffolding rings.